A dinâmica dos sistemas de produção praticados em uma unidade de conservação de uso direto na Amazônia - a Reserva Extrativista do Rio Cajari no estado do Amapá. - SOUSA, Walter Paixão de (2006)
This project approaches an specific type of extractivism: the extractivism of Brazil Nut made in the Extractive Reserve of Cajari river in the Amapá State (RESEX/CA). This project is a continuation of researches made in 2000, having as a main focus the understanding of the dynamic production systems used in RESEX/CA. In This project can be noticed that the changes occurred in the systems in a period from 2000 to 2005,more than economic, the remain of agricultural practicing related to the Brazil Nut extraction are ruled for other / different factors. The historical relation between the forest use with the extractivism and agricultural is very complex, thats the reason it can not be valued only by an economical prism. The information demonstrates that the extraction production units are those which have the smaller economical performance, although, there is not a movement of the families in erase this system. In the opposite/ In despite of, the extraction type had not just being keeper, but had improved/razed representatively from 2000 to 2005, showing attraction of this type to the families in RESEX/CA. However, the agro extractive systems had grown also, showing that some families want to achieve a higher quality level of life trough agriculture. About a direct use of conservation unit, to this extractive reserve must be directed support action for small farmers nut to the RESEX/CA, with the purpose that them may have a decent life, without expending in different activitys but extraction.